The Effect of Diode Laser on Viability and Antibiotic Sensitivity of Streptococcus mutans Isolated From Dental Caries - Saleh, Bushra H.; Ibrahim, Reem N.; Al-Ugaili, Dhafar N. (Iraqi Journal of Science, 2023)
Streptococcus mutans is one of the major cariogenic microbial flora. In an attempt to determine the mutagenic effect of diode laser on the viability and antibiotic sensitivity of this bacteria; A total of 30 samples were collected from dental caries. The isolates were identified using by conventional identification methods and confirmed using VITEK2 system. Twenty-one isolates were recorded as Streptococcus spp and ten of them were identified as Streptococcus mutans. Antibiotic susceptibility profile for Streptococcus mutans isolates against ten antibiotics was tested. The results revealed that all the isolates were resistant to cefixime and cephalothin, nine of them were resistant to erythromycin, ampicillin, and nalidixic acid, seven isolates were resistant to tetracycline and bacitracin, whereas all isolates were sensitive to chloramphenicol, ciprofloxacin and gentamycin. The effect of the diode laser on the isolates (S5 and S10) was tested at different time intervals (1, 2, 5, and 10) min. The viability of Streptococcus mutans isolates was affected by the obvious change in the behaviour of the bacteria from resistance to sensitivity after Laser exposure